Combined Aerobic Exercise with Intermittent Fasting Is Effective for Reducing mTOR and Bcl-2 Levels in Obese Females - Purwo Sri Rejeki; Adi Pranoto; Deandra Maharani Widiatmaja; Dita Mega Utami; Nabilah Izzatunnisa; Sugiharto; Ronny Lesmana; Shariff Halim (MDPI AG, 2024)
The integration of combined aerobic exercise and intermittent fasting (IF) has emerged as a strategy for the prevention and management of obesity, including its associated health issues such as age-related metabolic diseases. This study aimed to examine the potential of combined aerobic exercise and IF as a preventative strategy against cellular senescence by targeting mTOR and Bcl-2 levels in obese females. A total of 30 obese women, aged 23.56 ± 1.83 years, body fat percentage (FAT) 45.21 ± 3.73% (very high category), BMI 30.09 ± 3.74 kg/m2 were recruited and participated in three different types of interventions: intermittent fasting (IF), exercise (EXG), and a combination of intermittent fasting and exercise (IFEXG). The intervention program was carried out 5x/week for 2 weeks. We examined mTOR and Bcl-2 levels using ELISA kits. Statistical analysis used the one-way ANOVA test and continued with Tukey's HSD post hoc test, with a significance level of 5%. The study results showed that a combination of aerobic exercise and IF significantly decreased mTOR levels (−1.26 ± 0.79 ng/mL) compared to the control group (−0.08 ± 1.33 ng/mL; p ≤ 0.05). However, combined aerobic exercise and IF did not affect Bcl-2 levels significantly (−0.07 ± 0.09 ng/mL) compared to the control group (0.01 ± 0.17 ng/mL, p ≥ 0.05). The IF-only group, exercise-only group, and combined group all showed a significant decrease in body weight and fat mass compared to the control group (p ≤ 0.05). However, the combined aerobic exercise and IF program had a significant effect in reducing the total percentage of body fat and fat mass compared to the IF-only group (p ≤ 0.05). Therefore, it was concluded that the combined intermittent fasting and exercise group (IFEXG) undertook the most effective intervention of the three in terms of preventing cellular senescence, as demonstrated by decreases in the mTOR level, body weight, and fat mass. However, the IFEXG did not present reduced Bcl-2 levels.